Code Switching of Cinta Laura Khiel in Deddy Cobuzier Podcast - Dohona, Riskin Faoita; Rajagukguk, Rosdiana; Elfrida, Rotua (HUMAN: South Asian Journal of Social Studies, 2024)
Abstract. This study explores the phenomenon of code-switching as exhibited by Cinta Laura Kiehl during her guest appearance on Deddy Corbuzier's podcast. The primary aim is to examine the four types of code-switching—intra-sentential switching, inter-sentential switching, tag switching, and establishing continuity switches—using Hoffman's framework. The analysis, based on a specific episode of the podcast sourced from YouTube, aims to determine which type of code-switching is most dominant and explores its implications for bilingual communication. This qualitative research adopts a sociolinguistic perspective to analyze the role of language in interaction and cultural expression within a digital media context. Data were sourced from a specific episode of the podcast, focusing on the linguistic exchanges between Cinta Laura and Deddy Corbuzier. The findings are expected to contribute to a deeper theoretical understanding of bilingual communication and its relationship to identity construction in contemporary media. By isolating Cinta Laura’s linguistic practices, this study provides unique insights into her code-switching patterns and their significance within the Indonesian entertainment industry. The results hold relevance for academic discussions in linguistics and media studies, offering practical implications for educators, students, and researchers alike.Keywords: code-switching, intra-sentential, inter-sentential, tag switching, establishing continuity